Traditional, complementary and integrative medicine use among Indigenous peoples with diabetes in Australia, Canada, New Zealand and the United States - Alana Gall; Tamara L Butler; Sheleigh Lawler; Gail Garvey (Elsevier, 2021)
Abstract Objective: This systematic review aimed to describe traditional, complementary and integrative medicine (TCIM) use among Indigenous peoples with diabetes from Australia, Canada, New Zealand and the United States (US). Methods: A systematic search following the PRISMA (Preferred Reporting Items for Systematic Reviews and MetaAnalyses) statement guidelines was conducted. Data were analysed using meta‐aggregation. Results: Thirteen journal articles from 12 studies across Australia, Canada and the US were included in the review (no articles from New Zealand were identified). Indigenous peoples used various types of TCIM alongside conventional treatment for diabetes, particularly when conventional treatment did not meet Indigenous peoples' holistic understandings of wellness. TCIM provided opportunities to practice important cultural and spiritual activities. While TCIM was often viewed as an effective treatment through bringing balance to the body, definitions of treatments that comprise safe and effective TCIM use were lacking in the articles. Conclusions: The concurrent use of TCIM and conventional treatments is common among Indigenous peoples with diabetes, but clear definitions of safe and effective TCIM use are lacking. Implications for public health: Healthcare providers should support Indigenous peoples to safely and effectively treat diabetes with TCIM alongside conventional treatment.